2021
DOI: 10.3390/s21186282
|View full text |Cite
|
Sign up to set email alerts
|

Survey on Optical Wireless Communications-Based Services Applied to the Tourism Industry: Potentials and Challenges

Abstract: In this paper, we explore the potential applications of Optical Wireless Communications in the tourism industry, considering both indoor and outdoor scenarios and different transmission speeds. They range from high-speed atmospheric outdoor links (Free-Space Optics (FSO)) to indoor systems based on high-speed lighting networks (known under the trade name LiFi©) or low-speed services support the Internet of Things networks, using visible light (VLC) or IR emitters, with receivers based on either on classical ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 153 publications
0
10
0
Order By: Relevance
“…Data communication is a critical feature of wearable biosensors because it enables the real-time transmission of collected data to an external device, such as a smartphone . Wireless communication technologies, such as near-field communication (NFC), Bluetooth, Wi-Fi, and Zigbee, have been widely used in wearable biosensors. NFC, a form of wireless communication in close proximity, operates within a range of about 20 cm, facilitating the concurrent transmission of both power and data .…”
Section: Commercialization Aspectsmentioning
confidence: 99%
“…Data communication is a critical feature of wearable biosensors because it enables the real-time transmission of collected data to an external device, such as a smartphone . Wireless communication technologies, such as near-field communication (NFC), Bluetooth, Wi-Fi, and Zigbee, have been widely used in wearable biosensors. NFC, a form of wireless communication in close proximity, operates within a range of about 20 cm, facilitating the concurrent transmission of both power and data .…”
Section: Commercialization Aspectsmentioning
confidence: 99%
“…Therefore, smart tourism design supports the IoB in cocreating and connecting tourists' experiences via destination design and management (Xiang 2021) demonstrated that travelers could easily access integrated airport information, such as navigating airport facilities, obtaining recommended value-added services and enjoying special promotions via a machine-learning-driven mobile application that maps and tracks user's behavior and compares it with that of other users. Another example is Disney World Resort's MagicBand, which is a radio frequency identification (RFID) enabled wristband that consolidates visitors' park admission and hotel room access and customizes their purchase preferences (Aguiar-Castillo et al, 2021).…”
Section: Iob In Smart Tourism Destination Use Casesmentioning
confidence: 99%
“…On the other hand, in the rolling-shutter camera, the sampling rate is influenced by both the camera frame rate and rolling rate. VLC and LiFi have higher data rates owing to the use of photodiodes, whereas OCC has a lower data rate owing to the use of image sensors to receive the data [ 10 , 11 ]. Nevertheless, the OCC system is preferable for applications requiring environmental mobility and long-range usage.…”
Section: Introductionmentioning
confidence: 99%